Master’s Degree English Students’ Response to Abstract Writing: Issues and Challenges for Second Language Learners - Pokharel, Bishnu Prasad; Sharma , Balkrishna; Sapkota , Binod (Interdisciplinary Research in Education, 2024)
This paper examines the responses and reflections of five Master’s level students of the academic year of 2023-2024 majoring in English from Saraswati Multiple Campus, Kathmandu of Tribhuvan University, Nepal, to explore their performance of abstract writing in their thesis works. The purpose of this study was to assess the status and the area of possible improvement of abstract writing skills. Grounded in the primary data gathered from the interviews, a hermeneutic phenomenological study was done to infer lived experiences of those students regarding abstract writing during thesis writing. The study found that the students had struggled to produce a condensed and logically cogent abstract, revealing a gap between students’ performance and institutional instructional strategies in academic writing. It led to the conclusion that the lack of adequate departmental support and lax mentoring are responsible for students' performance gap in composing a logical abstract. This study recommends institutional support with ample authentic resources and guidelines for abstract writing during students’ thesis writing.